Ghosting pada User Experience Aplikasi Kencan Online Bumble Berdasarkan Pemikiran Homo Ludens di Universitas Udayana - Palgunadi, Ni Komang Trilita Sukma; Ranteallo, Ikma Citra; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
This research focuses on ghosting in the user experience of the Bumble online dating application at Udayana University. The purpose of this study is to analyze ghosting sociologically within the Bumble application, based on Johan Huizinga's Homo Ludens perspective. The findings indicate that the initial reasons students become users of the Bumble online dating application are (1) overcoming loneliness, (2) high curiosity, (3) building friendships, (4) recovering from a breakup, (5) needing someone to talk. The motives of students as Bumble users include: (1) seeking an outlet, (2) friend with benefits (FWB), (3) casual relationships (HTS), (4) making new friends, (5) establishing professional connections. The ghosting phase by students as Bumble users typically occurs when: (1) validation has been obtained, (2) sexual needs have been fulfilled, (3) the casual relationship phase is over, (4) avoiding emotional attachment, (5) differences in visions and goals arise. The act of ghosting in the user experience of the Bumble online dating application aligns with the characteristics of the Homo Ludens theory, which include freedom, being non-real, having specific locations and times, adhering to playing rules, and being autotelic.   Keywords: Ghosting, user experience, online dating, Bumble